2013
DOI: 10.5433/1679-0359.2013v34n6supl1p3553
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento, produção e qualidade dos frutos de pessegueiros enxertados sobre diferentes porta-enxertos

Abstract: ResumoO trabalho objetivou avaliar o vigor, a época de floração, a produção e a qualidade de pêssegos das cultivares Maciel e Chimarrita sobre os porta-enxertos Aldrighi, Capdeboscq, Flordaguard, Nemaguard, Okinawa e Umezeiro. O experimento foi conduzido a campo na Embrapa Uva e Vinho, em Bento Gonçalves/RS. As variáveis vegetativas e produtivas foram analisadas a campo e as análises físico-químicas dos frutos foram realizadas na Faculdade de Agronomia Eliseu Maciel (Universidade Federal de Pelotas -Pelotas/RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 5 publications
4
18
0
1
Order By: Relevance
“…These changes were shown by the higher contents of SS and of the SS/TA ratio in the fruits of 'Chimarrita' on 'Umezeiro', and by the higher pulp firmness, in the average of scions, induced by 'Umezeiro'. Comiotto et al (2013), while evaluating the same scions and rootstocks of the present study, did not observe any differences between rootstocks for SS, but found that 'Umezeiro' induced a lower SS/TA ratio than the other rootstocks. However, Orazem et al (2011) did report alterations in the maturation point due to rootstock effect.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…These changes were shown by the higher contents of SS and of the SS/TA ratio in the fruits of 'Chimarrita' on 'Umezeiro', and by the higher pulp firmness, in the average of scions, induced by 'Umezeiro'. Comiotto et al (2013), while evaluating the same scions and rootstocks of the present study, did not observe any differences between rootstocks for SS, but found that 'Umezeiro' induced a lower SS/TA ratio than the other rootstocks. However, Orazem et al (2011) did report alterations in the maturation point due to rootstock effect.…”
Section: Resultsmentioning
confidence: 75%
“…In 'Maciel' and 'Chimarrita', in most conditions assessed by Galarça et al (2013), 'Umezeiro' induced a lower pruning mass. However, Comiotto et al (2013), using the same combinations of scion/rootstock, did not observe any differences among rootstocks. At the end of present study, the rootstocks showed similar vegetative growth.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Both Aldrighi and Capdeboscq are the most commonly used rootstocks in the south of Brazil since it is easy to get their stones from industries to grow seedlings (Rocha et al, 2007). However, other rootstocks such as Flordaguard, Nemaguard, Okinawa, Umezeiro, Tsukuba and Seleção Viamão have been used as alternatives in terms of fruit adaptation, productivity and quality (Comiotto et al, 2012(Comiotto et al, , 2013Galarça et al, 2013).…”
Section: Introductionmentioning
confidence: 99%